Strengthening Character Education Of Students In Nonformal Education In Public Education - Achmad Muhajir (Yayasan Ilomata, 2021)
In order to carry out the mandate of the Law. No. 20 of 2003 as stated in PP no. 55 of 2007 concerning religious education and religious education is education that prepares students to be able to carry out roles that require mastery of knowledge about religious teachings and / or become experts in religious science and practice their religious teachings. Religious education also develops as a result of religious education subjects / courses which are considered to face various limitations. Especially at the public tertiary level where the religious education course only received a portion of 2 credits according to the decision of the Director General of Higher Education, Ministry of National Education Number: 43 / DIKTI / Kep / 2006. To overcome the shortage of religious learning, some people overcome it with additional religious education at homes, houses of worship, or in associations which then develop into formal, non-formal or informal religious education units or programs. As for the campus community, an innovation was carried out in the form of Diniyah Takmiliyah al-Jami'ah Education as a trap for the two credits that students were accepting in lectures.